Muslim women in law and society : annotated translation of Al-T'ahir Al-H'addad's Imra'tuna Fi 'l-sharica Wa 'l-mujtamac, with an introduction - 258596 Husni, Ronak; Newman, Daniel L. (New York, NY : Routledge, 2007)
01